Estate Planning by Agreement in the Sources of Roman Law - Grebieniow, Aleksander (Schöningh and Fink Early Modern and Modern History E-Books Online, Collection 2025., 2025)
This study presents Roman legal sources from the perspective of the broad concept of estate planning. The focus is on the presentation of those instruments for the voluntary transfer of assets in the event of death that are not wills or codicils. Contrary to popular belief, Roman law was not fundamentally opposed to the transfer of property mortis causa using contractual remedies. A look from the perspective of contemporary legal problems makes it possible to see the scope within which the Romans carried out such intergenerational transfers of wealth. The extent of this already ancient phenomenon and the diversity of dogmatic questions offers a notable starting point for discussions about the strength of today's inheritance law dogmas.